2014
DOI: 10.1007/s12031-014-0336-1
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Aging and Tumor Suppressor Protein Klotho Enhances Differentiation of a Human Oligodendrocytic Hybrid Cell Line

Abstract: Klotho functions as an aging suppressor, which, in mice, extends lifespan when overexpressed and accelerates development of aging-like phenotypes when disrupted. Klotho is mainly expressed in brain and kidney and is secreted into the serum and CSF. We have previously shown that Klotho is reduced in brains of old monkeys, rats, and mice. We further reported the ability of Klotho to enhance oligodendrocyte differentiation and myelination. Here, we examined the signaling pathways induced by Klotho in MO3.13, a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 50 publications
3
35
0
4
Order By: Relevance
“…Decreased KO dendritic complexity (Figure 2D,4F) suggests impaired maturation of immature neurons that resembles the phenotype of immature neurons from aged brain (Rao et al 2005). KL is also important for oligodendrocyte maturation (Chen et al 2015; Zeldich et al 2015), suggesting that trophic activity of KL could be required throughout the brain or that different forms of KL protein could have independent effects on different cell populations. Together data from the KO shows that the absence of immature neurons at 7 weeks (Figure 2A) is the product of progenitors failing to proceed through stages of differentiation and maturation causing suppression of neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased KO dendritic complexity (Figure 2D,4F) suggests impaired maturation of immature neurons that resembles the phenotype of immature neurons from aged brain (Rao et al 2005). KL is also important for oligodendrocyte maturation (Chen et al 2015; Zeldich et al 2015), suggesting that trophic activity of KL could be required throughout the brain or that different forms of KL protein could have independent effects on different cell populations. Together data from the KO shows that the absence of immature neurons at 7 weeks (Figure 2A) is the product of progenitors failing to proceed through stages of differentiation and maturation causing suppression of neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the authors have shown that Klt is co-localized with neuronal and oligodendrocyte markers but not with microglial and astrocyte markers. Chen et al [29] showed another important function of Klt in CNS. In CNS, Klt leads to the differentiation and maturation of oligodendrocyte progenitor cells to mature oligodendrocytes, but does not increase the proliferation of these cells.…”
Section: Neurons Oligodendrocytes and Kltmentioning
confidence: 99%
“…KL is a primarily type I transmembrane protein that is further processed to produce a secreted form with wide spectrum of tissue expression and functions [9]. KL has overlapping functions including the regulation of FGF23 signaling and subsequently affecting the regulation of calcium homeostasis and nitric oxide production [10], suppression of the insulin/insulin-like growth factor 1 (IGF-1) signaling [11], suppression of Wnt signaling and oxidative stress [12,13], oligodendrocyte maturation, and developmental myelination of the CNS and inhibition of cancer development [14]. The relationship of KL and human cancers is suggested by the observation of its downregulation in several cancer types through methylation of its promoter region [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%